(untitled) (Innovative professional education, 2025)
Vocational (vocational and technical) education plays a key role in training workers for the reconstruction of Ukraine. The main factors that influence the quality of vocational (vocational and technical) education are considered through the disclosure of the participation of the educational institution in projects, processes of modernization of the content, forms, means and structure of professional training of future qualified personnel for reconstruction